Persepsi Pengguna Terhadap Aplikasi Terintegrasi di Perpustakaan Universitas Andalas Menggunakan Metode End User Computer Satisfaction (EUCS) - Irawati, Vivi; Tri Anggraini, Julinda; Hafizulhaq, Fadli; Saputra, Andi (Ilmu Informasi Perpustakaan dan Kearsipan, 2025)
This study aims to evaluate the level of user satisfaction with the Mandiri Application in supporting the administration of the Library Exemption Certificate (SKBP) in higher education, using the EUCS (End-User Computing Satisfaction) model. The results show that the overall level of user satisfaction is at a high level, which can be seen from the five EUCS dimensions: content, accuracy, format, ease of use, and timeliness. The content dimension received the highest rating due to the relevance of data that supports the information needs of the SKBP, while the timeliness dimension shows satisfaction in terms of time efficiency. Nonetheless, there are significant differences in satisfaction levels based on user characteristics, particularly age and education level, where younger users and those with higher education levels tend to be more satisfied. The research constraint lies in the uneven distribution of respondents, resulting in quite striking variations in perceptions across several characteristics, such as faculty and education level. The results of this study show that the quality of technology, content, and the app's conformity to users' expectations have a positive effect on their satisfaction, and emphasise the importance of a more even distribution of respondents for future similar studies.